ANALYSIS OF THE FUTURE EVOLUTION OF MAXIMUM CUMULATIVES OF RAINFALL IN THE LOBO BASIN (CENTRAL-WEST OF COTE D’IVOIRE) - ALLECHY, Fabrice Blanchard; N’GUESSAN BI, Vami Hermann; YOUAN TA, Marc; ASSA YAPI, Fabrice; AFFIAN, Kouadio (Studia Universitatis Babeș-Bolyai Geographia, 2019)
This work study analyzes the future evolution of the maximum height of rains on three decades (2014-2023, 2024-2033 and 2034-2043). The WeaGETS third-order Markov model and calculation of climate index was respectively used to predict the field of daily rainfall for the period of 2014-2043 and to calculate three climate indices. The medium criterion of Nash 0.93 and the coefficient of determination medium R2 = 0.9994 for all the stations covering the zone of study shows a good performance of the Markov model. Annual maximum 1-day precipitation (Rx1day) and annual maximum consecutive 5-day precipitation (Rx5day) will decrease during the decades 2014 to 2023 and 2024 to 2033, and will increase from 2033 to 2043. While annual maximum consecutive 3-day precipitation (Rx3day) will know a decrease during the decade from 2024 to 2033 and an increase during the decades from 2014 to 2023 and from 2034 to 2043. Generally, the basin of Lobo will know an increase in these three climate indices over the entire period (2014-2043).